2023
DOI: 10.3390/ani14010047
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Analysis of a Parrot Bornavirus 2 Detected in a Sulphur-Crested Cockatoo (Cacatua galerita) Suggests a South American Ancestor

Ruy D. Chacón,
Christian J. Sánchez-Llatas,
Andrea J. Diaz Forero
et al.

Abstract: Parrot bornavirus (PaBV) is an RNA virus that causes Proventricular Dilatation Disease (PDD), neurological disorders, and death in Psittaciformes. Its diversity in South America is poorly known. We examined a Cacatua galerita presenting neuropathies, PDD, and oculopathies as the main signs. We detected PaBV through reverse transcription polymerase chain reaction (RT-PCR) and partial sequencing of the nucleoprotein (N) and matrix (M) genes. Maximum likelihood and Bayesian phylogenetic inferences classified it a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Taiwan strain NTUCL7 PaBV-4 has 95.89% sequence similarity with NPUSTIAVT-PaBV/Brain-2208023 and 99.7% sequence similarity with NPUSTIAVT-PaBV/Brian-2302010, while Taiwan strain NTUCL51 PaBV-2 has 97.80% sequence similarity with NPUSTIAVT-PaBV/Brain-2301024. Recently, phylogeographic analysis revealed that the South American ancestor could be the origin of PaBV-1, -2, and -8 genotypes [42]. This highlights the importance of further surveillance of Orthobornavirus for captive Psittaciformes, similar to Taiwan.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Taiwan strain NTUCL7 PaBV-4 has 95.89% sequence similarity with NPUSTIAVT-PaBV/Brain-2208023 and 99.7% sequence similarity with NPUSTIAVT-PaBV/Brian-2302010, while Taiwan strain NTUCL51 PaBV-2 has 97.80% sequence similarity with NPUSTIAVT-PaBV/Brain-2301024. Recently, phylogeographic analysis revealed that the South American ancestor could be the origin of PaBV-1, -2, and -8 genotypes [42]. This highlights the importance of further surveillance of Orthobornavirus for captive Psittaciformes, similar to Taiwan.…”
Section: Discussionmentioning
confidence: 98%
“…Since the first report of avian bornaviruses in 2008, there has been an increase in the number of countries reporting the presence of PaBV, a novel infectious viral agent causing proventricular dilatation disease affecting psittacine birds [1,11,14,[16][17][18][19]21,[35][36][37][38][39][40][41]. In Taiwan, the presence of PaBV has been known through the submitted sequences of the matrix protein (M) gene (MK736729.1-MK736782.1), nucleoprotein (N) gene (MK770085.1-MK770118.1), and PaBV-2 (OM933586.1), PaBV-4 (OM939725.1), and PaBV-5 (OM777141.1) complete genome in GenBank [42]. To further elucidate the PaBV presence in Taiwan, we screened feces samples from 124 psittacine birds collected for a year (June 2022 to May 2023), and demonstrated that 57 were PaBV-positive, with a prevalence of 45.97% and a low survival rate of 8.77%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation